2016
DOI: 10.1111/cfs.12295
|View full text |Cite
|
Sign up to set email alerts
|

Risk, resilience and identity construction in the life narratives of young people leaving residential care

Abstract: The role of residential care for children has developed very differently internationally, but in all cultural contexts there are questions about the extent to which it can help young people recover from high risk backgrounds. In the UK, residential care has come to be seen as the placement of last resort, yet new government guidance on permanence has suggested that residential care can provide security and a sense of belonging. Narrative analysis of interviews with 20 care leavers identified their different pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 17 publications
9
57
0
7
Order By: Relevance
“…Mentors were mentioned in regard to the contribution of their guidance to the young people, but the young people also referred to their constant and stable presence in their lives and to the emotional support they provide. Similar to the findings of Schofield, Larsson, and Ward (), some care‐leavers in the present study referred to mentors as substitutes for parents or other relatives. These findings stress the absence of parental figures and represent the ingrained desire of some care‐leavers for unconditional love and caring.…”
Section: Discussionsupporting
confidence: 90%
“…Mentors were mentioned in regard to the contribution of their guidance to the young people, but the young people also referred to their constant and stable presence in their lives and to the emotional support they provide. Similar to the findings of Schofield, Larsson, and Ward (), some care‐leavers in the present study referred to mentors as substitutes for parents or other relatives. These findings stress the absence of parental figures and represent the ingrained desire of some care‐leavers for unconditional love and caring.…”
Section: Discussionsupporting
confidence: 90%
“…Personal growth and development are important aspects of children's experience of residential care. In a study of young adults in the United Kingdom, Schofield, Larsson, and Ward () found important shifts in the identity of care leavers over time: for most, from being “bad” or a “victim” towards being a “survivor.” Among the processes that facilitated this shift were their capacity to exercise personal agency in their lives and being constructively engaged in education and work. A study by Gilligan () in Ireland linked engagement in extramural activities with improved educational performance.…”
Section: Young People's Experiences Of Being In Carementioning
confidence: 99%
“…The experience of being a member of a residential community is related to the Circle of Courage's theme of belonging (Lee & Perales, ). Schofield et al's (, p. 785) research found that belonging relationships “with parents, relatives, peers, foster carers, children's home and transitions staff” were central to identity development among looked‐after children. Their research also emphasizes the familial nature of these relationships, similar to findings from Van Breda () in South Africa, Sulimani‐Aidan (2016) in Israel, and Morantz and Heymann () in Botswana.…”
Section: Young People's Experiences Of Being In Carementioning
confidence: 99%
“…Children enter care at varying ages for a wide variety of reasons, and reside in a range of placements, but their primary needs are broadly similar. While much of the research and professional literature has focused on the need for state care to provide children with a sense of stability, security and love (Rees & Stein, 2016), there is a growing awareness of the need to promote children's sense of identity (Schofield et al, 2017) and pre-existing relationships with parents, siblings and significant others (Larkins et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Kiraly & Humphreys (2015), whether parents expect to resume the care of their children or not, there is a strong desire to remain in contact with their offspring. This is mirrored by children, who state that contact with their birth family and close friends is very important for them (Schofield et al, 2017).…”
Section: Introductionmentioning
confidence: 99%